Pengelolaan Bahan Berbahaya dan Beracun pada Perusahaan Migas X di Kabupaten Banggai : Studi Kasus pada Implementasi PP 74 Tahun 2001 Tentang Pengelolaan Bahan Berbahaya dan Beracun - Fahmi Basa; Lina Warlina; Hasrianti Hasrianti (Institut Nalanda, 2026)
This study evaluates the level of compliance of Hazardous and Toxic Materials (B3) management policies and practices at Oil and Gas Company X in Banggai Regency with the provisions of Government Regulation of the Republic of Indonesia Number 74 of 2001. The method used is content analysis of the company's internal documents (B3 management procedures, QHSSE policies, ERP, transportation safety) matched with key articles of PP 74/2001 (Chapter I; Chapter II; Chapter III Articles 11–20; Chapter V; Chapter VI; Chapter VIII), and enriched with qualitative data through cross-functional key informant interviews and worker surveys related to B3 implementation. The results show a high level of compliance in the aspects of SDS (Safety Data Sheet) obligations, transportation, packaging, storage with emergency response facilities, periodic health checks, and training accompanied by evidence of management support and community involvement programs. Gaps are seen in the complexity of internal procedures, capacity & load analysis of B3 warehouses, labeling, manual documentation, and community assistance mechanisms that have not been documented in specific procedures. Practical implications include procedural simplification, digitalization of SDS and inventory, increased warehouse capacity/zoning, standardization of GHS (Globally Harmonized System) labeling, and strengthening the integration of community assistance into the Emergency Response Plan (ERP). The findings indicate that Oil and Gas Company X is in the moderately compliant–highly compliant category with PP 74/2001, but requires targeted improvements to ensure effective, efficient, and sustainable compliance.